The Effects of Smoking and Obesity on ICSI Outcomes: A Retrospective Analysis - Bülent Haydardedeoğlu; Tayfun Çok; Esra Bulgan Kılıçdağ; Tayfun Bağış (Medical Network, 2010)
Cigarette smoking and obesity are both common health problems in developed and developing countries and are associated with an increased morbidity and mortality. The fecundity rate is found to be decreased by both smoking and obesity in unassisted reproduction in large epidemiologic studies. In the literature, the effects of obesity and smoking on ICSI are demonstrated separately. Our current study aims to reveal the effects of smoking together with obesity on ICSI outcomes. Our result showed that there was no statistically significant difference of outcomes between smokers and nonsmokers in all BMI groups which scheduled to GnRH Agonist ICSI cycle.